ANALISIS PERAWATAN RADAR GUNA MENINGKATKAN KELAIKLAUTAN TEKNIS DI KM. SABUK NUSANTARA 37 - Renida Nur Safriyuani; Aries Allolayuk; Chrisandi Rantegau Lande (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze radar maintenance in improving the technical seaworthiness of ships on KM. Sabuk Nusantara 37, a pioneer passenger and cargo vessel operating in West Sumatra waters. Radar is a critical electronic navigation device used to detect objects around the vessel, determine position, and support navigation decision-making, particularly under limited visibility conditions. This research employed a descriptive qualitative method, collecting data through direct observation, in-depth interviews with the Chief Officer and Second Officer, and documentation review during a 12-month sea practice period. Data were analyzed through stages of data reduction, data presentation, and conclusion drawing. The findings reveal three main factors contributing to the Koden radar failure: (1) damage to the PCB scanner and antenna caused by corrosion in the tropical marine environment; (2) maintenance practices that did not conform to the established checklist and manual book, including the absence of daily maintenance routines, cleaning performed only every two months, and inspection of the magnetron and scanner unit conducted only upon malfunction; and (3) the advanced operational age of the radar unit. Recommended optimization efforts include the consistent implementation of a Planned Maintenance System (PMS) encompassing daily checks, weekly cleaning and target detection tests, monthly inspections of critical components, and annual servicing by certified technicians as well as enhancing crew competency in radar operation and maintenance. This study affirms that radar reliability is directly linked to compliance with technical seaworthiness standards under SOLAS Chapter V and applicable national regulations.